God's People Made New : How Exploring the Bible Together Launched a Church's Spirit-Filled Future - Powell, Rachael J. (Book collections on Project MUSE., 2022)
God's People Made New reveals the role of God's Word in forming a congregation. Through the voices of congregants, biblical texts, theological reflection, and tools for studying the Bible, Rachael J. Powell inspires congregations to enter into the power of Scripture.